Models for Semiordered Data to Address Not Applicable Responses in Scale Measurement. Issue 2 (4th March 2018) - Huggins-Manley, Anne Corinne; Algina, James; Zhou, Sherry
Abstract : The purpose of this study is to develop and evaluate unidimensional models that can handle semiordered data within scale items (i.e., items with multiple ordered response categories, and one additional nominal response category). We apply the models to scale data with not applicable (NA) responses to compare the model performance to conditions in which NA responses are treated as missing and ignored. We also conduct a small simulation study based on the operational study to evaluate the parameter recovery of the models under the operational conditions. Findings indicate that the proposed models show promise for (a) reducing standard errors of trait estimates for persons who select NA responses, (b) reducing nonresponse bias in trait estimates for persons who select NA responses, and (c) providing substantive information to practitioners about the nature of the relationship between NA selection and the trait of measurement.